INTEGRASI HUKUM PAJAK DAN ZAKAT DI INDONESIA Telaah terhadap Pemikiran Masdar Farid Mas’udi - Zusiana Elly Triantini (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2013)
Masdar Farid Mas'udi is famous as an eclectic scholar who produces Islamic thought (ijtihad), which is becomes a subject of conversation among thinkers of Islam in Indonesia. The discourse of zakat and tax integration actually is not something new, but substantially, his thoughts can be used as a consideration of zakat and tax policies in Indonesia, and even become enlightened understanding of Islamic substance in Indonesia. His thoughts on integration of zakat and tax caused controversy and quite diverse questions. This even seems “strange” because he wanted to unite two things that are different substantially and usefulness. However, if we understand his thought more comprehensively both its content and his method of ijtihad, it would seem that his real thinking about tax and zakat unification substantially, can be a problem solution of zakat and tax implementation for Muslims in Indonesia. This paper will present ideas, methods and the formulations of zakat and tax’s concept of Masdar Farid Mas'udi.